IDENTIFIKASI KELIMPAHAN DAN KARAKTERISTIK FISIK MIKROPLASTIK PADA AIR PERMUKAAN DI KALI SURABAYA - Azkafia Alkafi Pasadzani; Syadzadhiya Qothrunada Zakiyayasin Nisa (Jurnal Rekayasa Teknik Sipil dan Lingkungan - CENTECH, 2026)
Surabaya River, a tributary of the Brantas River, serves as a source of raw water for community activities and needs, while also functioning as a discharge channel for industrial and domestic waste, potentially causing microplastic pollution. Microplastics are particles smaller than 5 mm that are resistant to degradation, leading to negative environmental impacts. This study aimed to identify the abundance and characteristics (shape, color, and size) of microplastics in the water column of the Surabaya River. Sampling was conducted at five stations using a purposive sampling method referring to SNI 8995:2021. Sample preparation followed the NOAA procedure, and particle identification was carried out using a digital microscope at 4x magnification. The results showed that microplastic abundance ranged from 69–181 particles/L, with non-uniform patterns across stations and depths. Fiber was the dominant type found at nearly all stations, followed by fragments and film. The particle colors identified were black and transparent, while the 1–3 mm size category was dominant across all stations. Depth differences did not consistently affect microplastic abundance, which was presumably more influenced by hydrodynamic conditions, anthropogenic activities around the river, and particle density.